Characterising and modelling free ammonia and ammonium inhibition in anaerobic systems - Astals, S.; Peces, M.; Batstone, D.J.; Jensen, P.D.; Tait, S. (Water research (Oxford), 2018)
Inhibition by ammoniacal nitrogen, consisting of free ammonia (NH3) and ammonium ion (NH4+), has been widely investigated for anaerobic digestion. However, despite the large amount of research on the subject, ammoniacal nitrogen inhibition still threatens many anaerobic digesters. This paper presents (i) a method to reliably characterise ammoniacal nitrogen inhibition and (ii) a robust inhibition modelling approach. Results showed that NH3 and NH4+ inhibition need to be jointly determined, which can only be done by performing inhibition tests at various total ammoniacal nitrogen (TAN) concentrations and pH values. These test conditions were reliably achieved using the salts NH4HCO3 and NH4Cl without pH adjustment, rather than by using NH4Cl with pH adjustment. The use of only salts showed a lower pH change during the inhibition test (∼1.5 days), thereby decreasing the uncertainty in TAN speciation and strengthening the test and model outputs. A threshold inhibition function satisfactorily described (R2 > 0.99) the joint inhibition of NH3 and NH4+ on three distinct inocula, and provided a better description of the inhibition testing results than a non-competitive inhibition function (R2 ∼0.70). The key advantage of the proposed threshold inhibition function is its capacity to identify the inhibition lower limit (concentration where inhibition starts; KImin) and upper limit (concentration where inhibition is complete; KImax). The threshold inhibition function also identifies the 50% inhibition concentration (KI50) at the midpoint of KImin and KImax. Finally, experimental and model results show that at pH 7.3–7.7 and TAN concentrations above 2000 mgN·L−1, both NH3 and NH4+ contribute significantly to overall inhibition. •Method to quantify free ammonia and ammonium inhibition on acetoclastic methanogens.•NH3 & NH4+ inhibition has to be jointly determined using various TAN and pH values.•NH4Cl and NH4HCO3 are preferred over NH4Cl with pH adjustment.•Under typical AD conditions, both NH3 and NH4+ contribute to inhibition.•A threshold inhibition function reliably describes NH3 and NH4+ inhibition.